Subjetividade plural no mundo contemporâneo - Lopes, João Teixeira (2012)
Based on the prolongued critique of Bernard Lahire to the theory of Pierre Boudieu's practice,a sociology of the dispositional and contextual complexity is defended, as well as the construction of methodologic devices capable to capture this plural subjectivity in situation; the sociological portraits, illustrated here by two researches coordinated by the author: one on the track of students in higher education (success, unsuccess and desertion) and another onfemale experiences in electronic music and dance scenes.